Sex differences in attention deficit hyperactivity symptom severity and functional connectivity of the dorsal striatum in young adults - Yu Chen; Guangfei Li; Jaime S. Ide; Xingguang Luo; Chiang-Shan R. Li (NeuroImage: Reports)
Attention deficit hyperactivity disorder (ADHD) occurs more frequently and manifests with greater symptom severity in men than in women. Although studies have implicated basal ganglia dysfunction, the functional connectivity (FC) of the dorsal striatum (DS), particularly in terms of sex differences, has not been fully investigated in ADHD. Here, using resting state fMRI data of a large sample of adults (n = 744; 395 women; 22–36 years) curated from the Human Connectome Project, we performed seed-based correlations for caudate and lentiform nucleus (LN) FC. ADHD symptom severity was quantified with the Achenbach Adult Self-Report ADHD total score as well as inattention and hyperactivity subscores. Imaging data were processed with published routines and evaluated at a corrected threshold. Men showed significantly higher ADHD total score than women. In men, inattention was negatively associated with LN FC with the right superior frontal gyrus. In women, inattention was negatively associated with caudate FC with the right inferior parietal gyrus and positively with LN FC with the left inferior frontal gyrus, and hyperactivity was positively associated with LN FC with a cluster in the dorsal anterior cingulate cortex and supplementary motor area. Sex differences in most of these connectivity patterns were confirmed by slope tests. Further, k-means clustering of FC's identified 3 groups each in men and in women. In men, group 1 showed higher inattention and hyperactivity than both group 2 and 3, and group 2 showed higher inattention than group 3. In women, group 1 showed higher inattention and hyperactivity than group 3 and higher inattention than group 2, and group 2 showed higher hyperactivity than group 3. These findings together suggest sex differences in DS FC as neural markers of ADHD and potentially of ADHD subtypes, with men and women each showing altered FC predominantly in the executive control and ventral attention/saliency networks.